Investigation of visitors’ distribution towards formulation of design planning guideline for Shanghai Haichan Ocean Park - Zhijia, Su; Wan Mohamed, Wan Srihani; Herman, Siti Sarah (Human Resource Management Academic Research Society, 2024)
The objective of this investigation is to explore the “The general layout of theme parks for the distribution of visitors” A case study of Shanghai Haichang Ocean Park. For the purpose of figuring out the optimum tourism carrying capacity of the theme parks’, attraction and spatial layout must be considered to assess its impact on visitor distribution, as a result to determine how park’s spatial layout impacts on the visitor motion. The research objective is to examine “The general layout of theme parks for the distribution of visitors” Method: use quantitative research method and primary method of data collection. Use questionnaire survey. Sample size was 250 Sample location: Shanghai Haichang Ocean Park. In the regression analyses, hypotheses were proven and it was found that each independent variable demonstrated the strongest contribution to the dependent variable. According to the outcome, the Cronbach Alpha for the collected data in this research is 0.835. Hence, the collected data and questionnaire used for this investigation are dependable and could further contribute to the future research. To a large extent, these discoveries could possibly impact theme park capacity planning and operations.